PERSEPSI MASYARAKAT DAN NILAI-NILAI TERHADAP PERINGATAN HAUL KI AGENG SINGOPRONO PADA BULAN SURA - Atika Lisamawati Nur Qoyyimah; Atiqa Sabardila (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
Nglebu Villagers’ perception produces an assessment on haul (day of death) as a commemoration once a year in the month of Suro. Value is something that is considered by an individual/group about good or bad for social life. Haul is an activity to commemorate the death of community figure or a figure in Islam proselytizing. This study aims to describe the Ki Ageng Singoprono haul procession, public perception on the Ki Ageng Singoprono haul culture, and the values contained in the Haul of Ki Ageng Singoprono commemoration. Miles & Huberman data analysis technique was used with four components: data collection, data reduction, data presentation, and drawing conclusions. Firstly, data collection was conducted by document analysis, observation, and interviews. Secondly, data reduction was done by recording data from observations. Thirdly, the presentation of data was done by the problem. Fourthly, conclusion was drawn after collecting data and analyzing the results of interviews. The results showed that 1) The Haul of Ki Ageng Singoprono procession contains 3 (three) series of events: people market, cultural carnival, and wayang kulit performance, 2) People think that the commemoration of haul is a form of respect to Ki Ageng Singoprono as Islam figure and considered as a guardian by people in Boyolai area, 3) The haul series contain religious values including instilling a spiritual soul by praying for Ki Ageng Singoprono and asking forgiveness for sins committed; social values including carrying out mutual cooperation activities to increase intimacy and brotherhood; cultural values including preserving the haul culture from one generation to the next; and economic value, namely participating in the haul of Ki Ageng Singoprono commemoration event where traders use it to sell any products in people's market or in carnival procession.